The Relationship Between Personal Hygiene And Skin Complaints In Orphanage Children In The Medan Area District - Lubis, Adhayani; Raja Siambaton, Michael Bahal; Oentari, Widyaningsih (Riviera Publishing, 2023)
Personal hygiene is a person's self-care to maintain cleanliness and health for physical and psychological well-being. Hygiene maintenance is necessary for individual comfort, safety, and health. One of a person's hygiene efforts is to care for skin hygiene. Low hygiene can be one of the precipitating factors for developing skin diseases. Orphanages are social institutions that accommodate, educate, and care for abandoned children, orphans, orphans, and orphans. Environmental conditions in the orphanage can cause many children to experience skin diseases, such as itching, heat or burning, bumps, and white patches, usually caused by the lack of clean water, alternating use of towels, and rarely changing bed linen and pillowcases. This study aimed to determine the relationship between personal hygiene and skin complaints in orphanages in Medan Area District. This research is analytical and uses a quantitative approach with a cross-sectional research design. This study used a sample of 77. Data in this study were collected through questionnaires and then analyzed using univariate and bivariate tests using Chi-Square. It was continued with validity and reality tests. Based on univariate tests, the majority of respondents have good personal hygiene. Based on bivariate tests using Chi-Square, it is known that the p-value is <0.05, so it can be concluded that there is a relationship between personal hygiene and skin complaints.